Mengoptimalkan Branding Desa Wisata Melalui Teknologi Tepat Guna QR Code - Eka Selfi Nur Jayanti; Ripka Suliandari; Virginia Mandasari; Daisy Marthina Rosyanti (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Optimizing Tourism Village Branding Through Appropriate Technology QR Code". With the aim that this technology can be used as a medium for conveying information to the wider community so that Sambirejo Village is better known and known for all its potential. Then so that the village is able to adapt to keep up with technological advances and it is hoped that by making village promotions using this QR Code, Sambirejo Village can become a village that is in great demand by the community as a tourist village and is known by the community as a creative and advanced village. The data needed in this study are primary and secondary data, as well as qualitative and quantitative data. Primary data is data obtained from direct observation and in-depth interviews with several important informants. Secondary data in this study were obtained from village records and literature surveys.